Letter from Clark Wissler to the director of the Hudson Bay Museum - Wissler, Clark, 1870-1947 (1946)
This archival material has been provided for educational purposes. Ball State University Libraries recognizes that some historic items may include offensive content. Our statement regarding objectionable content is available at: https://dmr.bsu.edu/digital/about